Pengaruh Produk, Promosi Dan Kualitas Pelayanan Terhadap Keputusan Anggota Menabung (Studi Kasus KSSP BMT Al-Fath Ikmi Di Kota Tangerang Selatan) - Rian Hidayatulloh; Koesmawan Koesmawan; Aris Muftie (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2019)
This study aims to determine the effect of products, promotions, and service quality on members' saving decisions (Case Study of KSPPS BMT Al-Fath IKMI in South Tangerang City). Both partially and simultaneously. The independent variables in this study are savings products, promotions, and service quality, the dependent variable in this study is the decision of members to save. The population in this study were members of KSPPS BMT Al-Fath IKMI in South Tangerang City. The population in this study amounted to 18,441 members, the sample in this study amounted to 377 respondents, the sampling technique used was random sampling, the data source used primary and secondary data, the data collection tool used was a questionnaire with a Likert scale. Based on the results of researchers, I was using quantitative methods with the method of analysis of Validity, Reliability, Classical Assumptions Test, Simple Linear Regression Test, Determination Coefficient Test (R2), Hypothesis Test. That savings products, promotions, and service quality The results of the research have a positive and significant effect on the decisions of members of savings (Case Study of KSPPS BMT Al-Fath IKMI in South Tangerang City). Give a good impact on members who make deposits.